From Minnesota to Mississippi: The Murder of George Floyd and the Retirement and Replacement of the State Flag of Mississippi - Caleb Smith; Stan Brunn; Byron D’Andra Orey (Práticas da História, 2023)
When voters make decisions about social issues, factors including cultural heritage, religion, race/ethnicity and recent events can intersect. However, the significance of visual images, historical narratives, media presentation, and future planning should not be overlooked. This article explores the importance of state flag histories and designs in Mississippi, specifically examining the 1894 flag design that became central to the state’s identity until voters approved a new design in 2020. The state’s flag politics are discussed within a prolonged national discourse with emphasis on recent racial attacks across the U.S. This study highlights calls for reform emanating from grassroots, media, religious, athletic, economic, social, and political groups in and outside the state. The article notes that racial tragedies such as the murder of George Floyd can serve as persistent inspiration of Mississippi voters and lawmakers to address inequalities and advance democracies.